PENGARUH KUALITAS PRODUK TERHADAP MINAT BELI PRODUK EAST TOAST DI KOTA SORONG - Febriyanti Valery Toisuta; Lili Sarce Joi Sapari; James Kastanya (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The number of consumers in January reached 62 people, while in February it fell to 35 people and then rose again in March with the number of consumers reaching 53 people. The data analysis technique used in this research is simple linear regression. The equation can be interpreted that: (1) The constant value (a) has a positive value of 7,571. a positive sign means that it shows a unidirectional effect between the independent variable variable (X) product quality and the dependent variable variable (Y) buying interest. This shows that the independent variable variable (X) product quality, has not changed (or has a value of 0), then the value of buying interest is 7.571; (2) The value of the simple regression coefficient is 0.347. This value shows a positive influence (straight line) with the dependent variable (variable y, buying interest). This means that if the independent variable variable (X) product quality has increased by 1%, then the dependent variable variable (Y) buying interest has increased by 0.347. Assuming that other variables remain constant, (3) the value of the T test is 4.261 if compared to the value of t table, with a df (degree of freedom) of, df = n – 1 = 50 – 1 = 49. Then obtained at t table of 2.00958, it can be determined that t count > t table (4.261 > 2.009) p. this can be interpreted that the hypothesis H0 is rejected and Ha is accepted, which means that there is an influence between the independent variable (X) product quality on the dependent variable variable (Y) buying interest.